Intervention on biofuels and the Japan WTO rice stock to stabilise world food prices - Galtier, Franck (Perspective, 2022)
Version française de l'article This issue n°59 is part of the Perspective series on Crises and food security. On international markets, prices of grains (wheat, maize) and vegetable oils (rapeseed, sunflower, soybean, palm) have been rising since mid-2020. Biofuels play a major part in this increase, and the war in Ukraine, which began in February 2022, has exacerbated it. Biofuels in fact link the price of these commodities to that of crude oil: when the crude oil price rises, the biofuels industry increases its demand for maize and vegetable oils. Temporarily limiting this industrial usage would reduce the price of these commodities. Moreover, in case of an increase in rice prices, one solution would be to authorise Japan to export the rice stock it has built up under World Trade Organization (WTO) rules. In order to prevent future crises, these two levers could be activated as soon as world prices of these agricultural commodities reach predetermined levels.